Genetic analysis of the CITED2 gene promoter in isolated and sporadic congenital ventricular septal defects. Issue 4 (13th January 2021) - Zheng, Si‐Qiang; Chen, Huan‐Xin; Liu, Xiao‐Cheng; Yang, Qin; He, Guo‐Wei
Abstract: Ventricular septal defect (VSD) is the most common congenital heart defect. Previous studies have reported genetic variations in the encoding region of CITED2 highly associated with cardiac malformation but the role of CITED2 gene promoter variations in VSD patients has not yet been explored. We investigated the variation of CITED2 gene promoter and its impacts on gene promoter activity in the DNA of paediatric VSD patients. A total of seven variations were identified by Sanger sequencing in the CITED2 gene promoter region in 400 subjects, including 200 isolated and sporadic VSD patients and 200 healthy controls. Using dual‐luciferase reporter assay, we found four of the 7 variations identified significantly decreased the transcriptional activity of the CITED2 gene promoter in HEK‐293 cells ( P < .05). Further, a bioinformatic analysis with the JASPAR databases was performed and a cluster of putative binding sites for transcription factors was created or disrupted by these variations, leading to low expression of CITED2 protein and development of VSD. Our study for the first time demonstrates genetic variations in the CITED2 gene promoter in the Han Chinese population and the role of these variations in the development of VSD, providing new insights into the aetiology of CHD.